One-year real-world experience with mavacamten and its physiologic effects on obstructive hypertrophic cardiomyopathy - Kim, Daniel Seung; Chu, Emily L.; Keamy-Minor, Emily E.; Paranjpe, Ishan Dhananjay; Tang, Wilson L.; O’Sullivan, Jack W.; Desai, Yaanik B.; Liu, Michael B.; Munsey, Elise; Hecker, Kimberly; Cuenco, Isabella; Kao, Beth; et al. (Frontiers in Cardiovascular Medicine, 2024)
Mavacamten is a first-in-class cardiac myosin ATPase inhibitor, approved by the United States Food and Drug Administration for the treatment of hypertrophic cardiomyopathy with obstructive physiology (oHCM). Here, we present the real-world use of mavacamten in 50 patients with oHCM at a tertiary care referral center. In both our highlighted case and in our aggregate data, we report significant improvement in wall thickness, mitral regurgitation, left ventricular outflow tract obstruction and New York Heart Association symptom class. Moreover, in our center’s experience, neither arrhythmia burden, nor contractility have worsened in the vast majority of patients: we note a clinically insignificant mean decrease in left ventricular ejection fraction (LVEF), with only two patients requiring temporary mavacamten discontinuance for LVEF < 50%. Adverse events were rare, unrelated to mavacamten itself, and seen solely in patients with disease too advanced to have been represented in clinical trials. Moreover, our multidisciplinary pathway enabled us to provide a large number of patients with a novel closely-monitored therapeutic within just a few months of commercial availability. These data lead us to conclude that mavacamten, as a first-in-class cardiac myosin inhibitor, is safe and efficacious in real-world settings.